Research on Aluminium Alloy AlCu4Mg Surface Machined by Abrasive Water Jet - Muller, Miroslav; Valasek, Petr (Manufacturing Technology Journal, 2017)
The paper deals with a machining of the aluminium alloy by means of an unconventional technology, i.e. an abrasive water jet (AWJ). The paper deals with a study of an influence of the abrasive water jet at its impact on a surface of the machined material, i.e. the aluminium alloy AlCu4Mg of a thickness 20 mm. A topography of the machined surface is evaluated within the research by means of roughness parameters. A surface analysis is also evaluated by means of a scanning electron microscopy (SEM) depending on a cutting speed and a mass flow of the abrasivum. The research results proved an increased influence of the cutting speed and the mass flow of the abrasivum. The optimum cutting speed was 50 mm.min-1, the cut was uniform without a significant grooved zone typical for cuts by means of AWJ technology.
Keywords: cutting speed; gap width; mass flow of abrasivum; SEM; surface roughness